(untitled) (Journal of Medical Sciences, 2021)
A transmembrane protein known as FNDC5 was identified in skeletal muscle, the heart, and the brain in 2002. A paper in 2012 described a cleaved protein called irisin is generated in response to exercise and may mediate some of exercise’s positive benefits. Many articles have been published since then that have looked at the roles of irisin. Adipose tissue and metabolism have piqued researchers’ attention because of their roles in the browning of white adipose tissue, which improves glucose homeostasis, obesity, type 2 diabetes, and atherosclerosis. Irisin’s possible functions in bone remodelling and the brain have recently been discovered, including consequences that might be linked to Alzheimer’s disease. Using novel markers to define disease pathophysiology reveals essential areas of concern for earlier diagnosis. Resulting in better treatment approaches and preventative strategies for illnesses affecting humans. This review examines various yet-to-be-determined applications and inconsistencies. We critically analyze current information and outline alternative ways to overcome existing uncertainties.